Gender dan identitas dalam sastra di mata remaja - Sandya Rani; Wening Udasmoro (Masyarakat, Kebudayaan dan Politik, 2015)
Young adult literature is one of the literary genre which implied teenage audience or adolescent. It is often confused with what can be exactly considered as children literature. Adolescence as a group of age, is placed in between childhood and adult people. Through an adolescent fiction, Lupus, this research sees gender as an effect and as a tool which could influence the adolescent’s identity. Based on theory of social practice, the things that are usually done by the teenagers in everyday life will be considered as a common sense although it is opposed to normative matters, such as a choice of their gender role. Adolescent readers in this case, are not fully aware of gender and identity, but they define those things related to the construction of sociocultural context.